IDEOLOGICAL DISCOURSES ON ENVIRONMENT IN BALI TOURISM DEVELOPMENT - Ni Gst Nym Suci Murni; I Gede Mudana; Dewa Made Suria Antara (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
The environment is increasingly occupying important issues in all aspects of life including the tourism business that is often highlighted to ignore the environment. Because it is so crucial, it is constantly discoursed not only in local and national contexts but more globally. In these evolving discourses, it turns out that there are a number of ideologies that show the interests of those who discoursing them. This research uses qualitative approach, and scientifi cultural studies paradigm. The purpose of this research is to know the ideologies of global, national and local environmental discourse. Research results show that based on the global ideology of sustainable development, there are ecological sustainability, economic sustainability, and social sustainability. Ideology of national environmental discourse which is a transformation from developmentalism ideology (modernization) can also hegemonize company industry, society, with legitimizing by law and regulations issued about tourism and environment, so that the sustainability of development can be achieved. The ideology of local environmental discourse there are various local knowledge (local genius) related to the environment that has been practiced by certain countries, especially the developing countries, where tourist destination areas such as Bali have run it through religious ritual, as well as through the daily life of the community .